Role of School Princpal In The Development of Scholl Management (A Study at SDIT Cahaya Hati Bukittinggi) - Ali Mutasar (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This research aims to find out the role of school principle in the development of school management as an effort to realize Islamic school achievement, a study at SDTI Hati, Bukittinggi. Education quality need role of head master to made many program to increase of education management to realize a school that is high-achieving and Islamic. In this research, researcher uses the qualitative descriptive method, and to get of data, researcher use observation, interview and document. Finding of research, the head master in SD Islam Terpadu Cahaya Hati in Bukittinggi create many program to increase of education quality that Islamic. These programs include management curriculum, student, teachers and employee, financial, infrastructure, special service, and relationship with communities and parents.